Earnings Expectations of "First-in Family" University Students and Their Role for Major Choice - Katharina Adler; Fabian Kosse; Markus Nagler; Johannes Rincke (CESifo GmbH, 2025)
How do students' earnings expectations differ by being the first in their family to attend university (FiF) and how do they affect field of study choice? We leverage unique survey and administrative data from a German university to document sizable gaps in expected earnings between FiF and non-FiF students. Our data can explain two-thirds of this gap, with the largest share attributable to field of study choice. We show that FiF students sort less into study fields based on their earnings expectations. Investigating potential explanations, we find that they expect lower own ability and worse non-wage amenities in high-earning fields.
Keywords: I23; I24; I26; J24; 330; socio-economic gaps; first-generation; higher education; earnings expectations